DISTRIBUSI SEDIMEN PADA WADUK JATIBARANG, KOTA SEMARANG - Fitria Maya Lestari; Ratih Pujiastuti; Risdiana Cholifatul Afifah (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2024)
The main issue in the operation of reservoirs is sedimentation. This can lead to silting and affect the reservoir's storage capacity. The distribution of sediments needs to be understood in order to gain an overview of their spread, so that measures can be taken to address sediment-related issues in the Jatibarang Reservoir. The analysis was conducted using sediment data from previous studies, which reported a total sediment volume of 6.64 million m³ over a period of 50 years. Based on topographic data, it was found that the Jatibarang Reservoir is classified as Type III, with a